Echocardiographic findings in 2261 peri-pubertal athletes with or without inverted T waves at electrocardiogram. Issue 3 (7th November 2014) - Calò, Leonardo; Sperandii, Fabio; Martino, Annamaria; Guerra, Emanuele; Cavarretta, Elena; Quaranta, Federico; Ruvo, Ermenegildo de; Sciarra, Luigi; Parisi, Attilio; Nigro, Antonia; Spataro, Antonio; Pigozzi, Fabio
Abstract : Objective: T wave inversion (TWI) has been associated with cardiomyopathies. The hypothesis of this study was that TWI has relevant clinical significance in peri-pubertal athletes. Methods: Consecutive male soccer players, aged 8–18 years, undergoing preparticipation screening between January 2008 and March 2009 were enrolled. Medical and family histories were collected; physical examinations, 12-lead ECGs and transthoracic echocardiogram (TTE) were performed. TWI was categorised by ECG lead (anterior (V1–V3), extended anterior (V1–V4), inferior (DII–aVF) and infero-lateral (DII–aVF/V4–V6/DI-aVL)) and by age. Results: Overall, 2261 (mean age 12.4 years, 100% Caucasian) athletes were enrolled. TWI in ≥2 consecutive ECG leads was found in 136 athletes (6.0%), mostly in anterior leads (126/136, 92.6%). TWI in anterior leads was associated with TTE abnormalities in 6/126 (4.8%) athletes. TWI in extended anterior (2/136, 1.5%) and inferior (3/136, 2.2%) leads was never associated with abnormal TTE. TWI in infero-lateral leads (5/136, 3.7%) was associated with significant TTE abnormalities (3/5, 60.0%), including one hypertrophic cardiomyopathy (HCM) and two LV hypertrophies. Athletes with normal T waves had TTE abnormalities in 4.4% of cases, including one HCM with deep Q waves in infero-lateral leads. Conclusions: In this broad population of peri-pubertal male athletes, TWI in anterior leads was associated with mild cardiac disease in 4.8% of cases, while TWI in infero-lateral leads revealed HCM and LV hypertrophy in 60% of cases. ECG identified all cases of HCM.